Clean the Sprayer to Avoid Crop Injury - Frederick M. Fishel (EDIS)
The objective of this 5-page document is to present the correct clean-out procedure for spray equipment following pesticide use. Written by Frederick M. Fishel and published by the UF/IFAS Agronomy Department, August 2018. http://edis.ifas.ufl.edu/pi277